Translanguaging Approach in English Speaking Classroom: A New Trend in Language Teaching - Châu Nguyễn Hoàng Long,; Trần Quốc Thao, (Journal of Technical Education Science, 2025)
The translanguaging approach is becoming increasingly important in today’s multilingual English teaching contexts, particularly in English Speaking Classrooms (ESC). Unlike traditional methods that use only English, translanguaging allows students to incorporate their native language and other languages they know to support their English comprehension and communication. This inclusive strategy enables learners to understand complex ideas more effectively by drawing from familiar linguistic frameworks, which helps ease cognitive load and boost understanding. Additionally, it builds adaptable linguistic skills and confidence, as students become more comfortable moving between languages. This paper presents both the theory and practice of translanguaging within English as a Foreign Language (EFL) settings and ESC. It discusses the evolving role of English, the rise of translanguaging, and insights from teachers and students in ESC. The article also reviews recent studies on translanguaging in EFL, addressing its benefits and challenges, and concludes with practical strategies and pedagogical recommendations for EFL teachers in bilingual or multilingual classrooms.